Eine neue phonetische Hypothese zum primären Umlaut von germ. */a/ im Althochdeutschen - Panieri, Luca (Linguistik Online, 2013)
This paper is concerned with the origin of the so-called Old High German primary umlaut. Even if this question has long been discussed, debate on this subject is still open. It seems however that scholars, though not agreeing with each other, mostly accept the standard theory's assumption of the existence of two kinds of short e in Old High German, of which the one derived from an umlauted germ. */a/ is taken to be higher than the one derived directly from germ. */e/, usually denoted by 〈ë〉 in handbooks and grammars. While thinking that there is indeed no reason to doubt that German had at a certain time set up a phonological opposition between, respectively, [e] and [ε], the apparent phonetic paradox of the rise of the former and more closed vowel starting from an ancient very open [a] still remains: how could [a] develop into [e] without running across the [ε]? This paper gives a new phonetic solution to this problem, which is able to account for such enfants terribles as OHG thanchandi/thenkendi (< germ. *þankijanđ-), both found in the same manuscript.